Method for manufacturing electrode, electrode, and battery

By coating carbon particles with resin in the liquid battery electrode and mixing with fibrated PTFE, the problem of insufficient electrode monomer capacity in the liquid battery is solved, and higher monomer capacity and lower manufacturing cost are achieved.

CN119480927APending Publication Date: 2025-02-18TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410732105.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-06-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the case of application in liquid batteries, there is room for improvement in the existing electrode monomer capacity.

Method used

The electrode is made by coating at least a portion of the surface of the carbon particles with a resin and mixing the resin-coated carbon particles with polytetrafluoroethylene (PTFE), and then fibrosis of the PTFE.

Benefits of technology

This method significantly improves the monomer capacity in liquid batteries, inhibits excessive formation of solid electrolyte interfaces, maintains sufficient monomer capacity, and reduces manufacturing costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004880508050000071
    Figure BDA0004880508050000071
Patent Text Reader

Abstract

A method for manufacturing an electrode used in a battery containing an electrolyte solution, the method comprising: a step for coating at least a portion of the surface of carbon particles with a resin; a step for obtaining a mixture by mixing the resin-coated carbon particles with polytetrafluoroethylene; and a step for fiberizing the polytetrafluoroethylene in the mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing an electrode, an electrode, and a battery. Background Art

[0002] In batteries such as lithium ion secondary batteries, electrodes are used in which active material particles are fixed on the surface of a current collector such as a metal foil with a binder. As a method for manufacturing an electrode, there is a known method of coating a composition prepared by mixing active material particles and a binder with a solvent on the surface of a current collector (also referred to as a wet method). In addition, there is a known method of fixing active material particles to a current collector using a binder without using a solvent (also referred to as a dry method).

[0003] As a method for manufacturing an electrode based on a dry method, a method for using a resin having a property of fibrillation (fibrillation) when a shear force is applied as a binder is proposed. For example, the following method for manufacturing an electrode is described in Japanese Patent Application No. 2022-3694. The PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to make an electrode film. Then, the electrode film is integrated with a collector to manufacture an electrode. Summary of the invention

[0004] When the electrode obtained by the method described in Japanese Patent Application Laid-Open No. 2022-3694 is applied to a battery using an electrolyte solution (also referred to as a liquid battery), there is room for improvement in the single cell capacity. An embodiment of the present disclosure aims to provide a method for manufacturing an electrode having excellent single cell capacity when used in a liquid battery, an electrode having excellent single cell capacity when used in a liquid battery, and a battery including the electrode.

[0005] Means for solving the above-mentioned problems include the following embodiments. <1> A method for manufacturing an electrode, the electrode being an electrode used in a battery containing an electrolyte, the manufacturing method comprising: A step of coating at least a portion of the surface of the carbon particles with a resin; A step of mixing carbon particles coated with a resin and polytetrafluoroethylene to obtain a mixture; and The step of fiberizing the polytetrafluoroethylene in the mixture. <2> according to <1> The method for producing an electrode as described above, wherein: The coverage rate of the carbon particles by the resin is 3% or more. <3> An electrode is an electrode used in a battery containing an electrolyte. It includes a current collector and an electrode layer, The electrode layer includes carbon particles at least a portion of the surface of which is coated with a resin, and fibrous polytetrafluoroethylene. <4> according to <3> The electrode described herein, wherein The coverage rate of the carbon particles by the resin is 3% or more. <5> A battery having <3> or <4> The electrodes and electrolytes described herein.

[0006] According to one embodiment of the present disclosure, there are provided a method for manufacturing an electrode having excellent single cell capacity when applied to a liquid battery, an electrode having excellent single cell capacity when applied to a liquid battery, and a battery including the electrode. DETAILED DESCRIPTION

[0007] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment. In the present disclosure, the term "process" is not limited to an independent process, and is also included in the term as long as the intended purpose of the process can be achieved even if it cannot be clearly distinguished from other processes. In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, when there are plural kinds of substances corresponding to each component, the amount of each component means the total amount of the plural kinds of substances unless otherwise specified. Electrode manufacturing method

[0008] The electrode manufacturing method disclosed herein is a method for manufacturing an electrode used in a battery containing an electrolyte. The manufacturing method includes: a step of coating at least a portion of the surface of carbon particles with a resin; a step of mixing the carbon particles coated with the resin and polytetrafluoroethylene to obtain a mixture; and a step of fiberizing the polytetrafluoroethylene in the mixture.

[0009] When applied to a liquid battery, the electrode produced by the method of the present disclosure exhibits superior single-cell capacity compared to an electrode formed of a mixture of carbon particles whose surfaces are not coated with a resin and PTFE. The reason for this is considered to be, for example, as follows. In an electrode produced by fibrillating PTFE contained as a binder together with carbon particles, the contact area between carbon particles and the binder is smaller than that of an electrode obtained by other methods (wet method, electrostatic method, etc.), and the area of ​​the exposed surface of the carbon particles is larger. Therefore, during the initial charge and discharge of the battery, a large amount of a film called a solid electrolyte interface (SEI) is formed on the surface of the carbon particles. SEI has the function of inhibiting the decomposition of the electrolyte, etc. However, excessive formation of SEI leads to an increase in irreversible capacity (ie, a decrease in the single cell capacity) caused by the immobilization of lithium ions. In the method disclosed herein, an electrode is produced using carbon particles at least a portion of the surface of which is coated with a resin. Thus, excessive formation of SEI on the surface of the carbon particles is suppressed, and sufficient single-body capacity is maintained.

[0010] According to the method disclosed in the present invention, an electrode can be manufactured without using a solvent. Therefore, the method disclosed in the present invention is also advantageous in reducing the manufacturing cost of the electrode and reducing the impact on the environment and organisms.

[0011] Hereinafter, the process of coating at least a portion of the surface of the carbon particles with resin is also referred to as "process 1". The process of mixing the carbon particles coated with resin and PTFE to obtain a mixture is also referred to as "process 2". The process of fibrillating the PTFE in the mixture is also referred to as "process 3". Process 1

[0012] In step 1, at least a part of the surface of the carbon particles is coated with a resin. The type of carbon particles used in this step is not particularly limited and can be selected from materials generally used as negative electrode active materials.

[0013] Specific examples of the material of the carbon particles include graphite, soft carbon, hard carbon, etc. The carbon particles may be secondary particles formed by aggregation of a plurality of primary particles. The carbon particles used in the production of the electrode may be one kind alone or two or more kinds. The volume average particle size of the carbon particles is not particularly limited, and can be selected from the range of 5 μm to 30 μm, for example.

[0014] In the present disclosure, the volume average particle size of particles is a value (D50) at which the accumulation from the smaller diameter side becomes 50% in the volume-based particle size distribution measured by a laser diffraction scattering method.

[0015] In this step, the type of resin used for covering the carbon particles is not particularly limited, and can be selected from materials generally used in the production of batteries. Specific examples of the resin include polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate. The resin used in this step may be a single type or two or more types. From the viewpoints of adhesive strength, affinity with PTFE, resistance to electrolyte, and the like, polyvinylidene fluoride (PVdF) is preferably used as the resin.

[0016] From the viewpoint of ensuring sufficient monomer capacity, the coverage rate of the carbon particle surface with the resin is preferably 3% or more, more preferably 5% or more, and even more preferably 10% or more. The coverage rate of the resin on the surface of the carbon particles may be 60% or less, 50% or less, or 40% or less.

[0017] The coverage rate of the carbon particle surface with the resin was measured by an image analysis method. As an image analysis method, for example, a method of performing F mapping using energy dispersive X-ray spectroscopy (EDX) can be cited. Specifically, carbon particles coated with resin are observed using a scanning electron microscope (SEM), and F mapping is performed using EDX. Region X corresponding to the carbon particles and region Y where the resin (F) exists in region X are binarized, and the coverage is calculated according to the following formula. Coverage (%) = (area of ​​Y / area of ​​X) × 100

[0018] In this step, the method of coating at least a part of the surface of the carbon particles with the resin is not particularly limited, and the method can be carried out by a known method. For example, a composite treatment may be performed in which carbon particles and a resin are kneaded using a mixer or the like to coat at least a portion of the surface of the carbon particles with the resin. The amount of the resin per 100 parts by mass of the carbon particles can be selected from the range of, for example, 1 part by mass to 20 parts by mass, or 2 parts by mass to 10 parts by mass. Process 2

[0019] In step 2, the carbon particles coated with the resin and PTFE are mixed to obtain a mixture. The mixing method is not particularly limited, and the mixing can be carried out using a known method. The amount of PTFE in the mixture relative to 100 parts by mass of the carbon particles can be selected from the range of, for example, 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass.

[0020] The PTFE mixed with the carbon particles in step 2 may be in a granular form. The mixture obtained in step 2 may not contain a solvent. In step 2, at least a part of the PTFE may be fibrillated, and granules in which carbon particles are bound together by the fibrillated PTFE may be produced.

[0021] The mixture of carbon particles coated with resin and PTFE may contain a binder other than PTFE. As the binder other than PTFE, for example, it can be selected from the resins used for coating carbon particles mentioned above. When the mixture contains a binder other than PTFE, the content thereof may be 20 parts by mass or less, 10 parts by mass or less, or 5% by mass or less, relative to 100 parts by mass of PTFE.

[0022] The mixture of the carbon particles coated with the resin and PTFE may also contain a conductive material. Specific examples of the conductive material include carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes and other carbon materials. When the mixture contains a conductive material, the content thereof can be selected from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass, based on 100 parts by mass of the carbon particles. Process 3

[0023] In step 3, the PTFE in the mixture obtained in step 2 is fiberized. The method of fibrillating PTFE is not particularly limited, and the method can be carried out using a known method. From the viewpoint of workability when integrating the mixture after PTFE fiberization with the current collector, it is preferred to fiberize PTFE and form the mixture into a sheet in step 3. As a method of forming PTFE into fibers and shaping the mixture into a sheet, for example, a calendering treatment using a roll press can be mentioned.

[0024] The thickness of the formed body obtained by forming the mixture into a sheet is not particularly limited and can be adjusted according to the desired thickness of the electrode layer. For example, the thickness of the formed body can be selected from the range of 10 μm to 200 μm.

[0025] In step 3, the mixture obtained by fiberizing PTFE, preferably a sheet-shaped molded body, is integrated with a current collector to form an electrode. The method of integrating the mixture after PTFE fiberization with the current collector is not particularly limited, and it can be implemented by using a known means. For example, a roller press, a flat plate press, etc. can be used to press the mixture and the current collector. The material of the current collector is not particularly limited, and it can be selected from known materials such as aluminum, copper, nickel, titanium, and stainless steel. electrode

[0026] The electrode disclosed in the present invention is an electrode used in a battery containing an electrolyte. The electrode includes a current collector and an electrode layer. The electrode layer includes carbon particles at least a portion of the surface of which is coated with a resin, and fibrous polytetrafluoroethylene (PTFE fiber).

[0027] Compared with an electrode including carbon particles and PTFE fibers whose surfaces are not coated with a resin, the electrode of the present disclosure exhibits excellent single-cell capacity.

[0028] The details and preferred aspects of the electrode and each material contained in the electrode of the present disclosure are the same as the details and preferred aspects of the electrode produced by the above-mentioned method for producing an electrode and each material used therein.

[0029] The electrode of the present disclosure may further include a member other than the current collector and the electrode layer including the active material particles and the PTFE fiber. For example, the electrode of the present disclosure may further include an electrode layer that does not include the PTFE fiber. Battery

[0030] The battery of the present disclosure includes the electrode of the present disclosure and an electrolyte. The battery of the present disclosure includes the electrode of the present disclosure as a negative electrode.

[0031] The type of the electrolyte contained in the battery is not particularly limited, and can be selected from electrolytes generally used in liquid batteries.

[0032] The type of battery disclosed herein is not particularly limited and may be selected from batteries such as lithium ion secondary batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, cobalt-titanium-lithium secondary batteries, and sodium ion secondary batteries.

[0033] Hereinafter, the present disclosure will be described in further detail using examples, but the present invention is not limited to these examples. Example: Preparation of negative electrode

[0034] The following materials were charged into an MP mixer (Japan COKE & ENGINEERING Co., Ltd.) in the amounts shown in Table 1, and composite treatment was performed at 10,000 rpm for 10 minutes to coat the surface of the carbon particles with a resin. Carbon particles: graphite (volume average particle size: 20 μm) Resin: PVdF

[0035] PTFE was further added to the MP mixer after the composite treatment, and mixed at 300 rpm for 180 seconds, and then further mixed at 5000 rpm for 500 seconds to form granules in which carbon particles were bound together by fibrillated PTFE.

[0036] The mixture including the granules was rolled using a roll press (linear pressure: 0.4 t / cm) to fiberize the PTFE and form it into a sheet (thickness: 200 μm). The sheet-shaped molded body and a copper foil (thickness: 8 μm) as a current collector were bonded together using a flat plate press (load: 5 t, 160° C.).

[0037] Through the above steps, a negative electrode is obtained in which a negative electrode layer including carbon particles at least a part of the surface of which is coated with a resin and PTFE fibers is disposed on a current collector. Comparative Example: Preparation of Negative Electrode

[0038] A negative electrode was produced in the same manner as in Example 1 except that the composite treatment of the carbon particles was not performed. Evaluation of coverage

[0039] The carbon particles after the composite treatment were observed by SEM, and F mapping was performed by EDX attached to the SEM to calculate the coverage rate of the carbon particles with the resin. The results are shown in Table 1. Evaluation of Monomer Capacity

[0040] A small-sized cell was prepared using the negative electrode prepared in the examples and comparative examples and the positive electrode prepared by the following method. As the electrolyte, a 1.14 M LiPF 6 A mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (EC:DMC:EMC=30:34:36, volume %). The discharge capacity of the prepared small-sized monomer was measured by the following method. The results are shown in Table 1. Measurement method: CCCV was performed at a current value of 0.3 C in the range of 4.25 V to 2.5 V (cut-off current: 1 / 20 C), and the discharge capacity (mAh / g) was calculated. Preparation of positive electrode

[0041] A paste containing NCM (97.5 parts by mass) as a positive electrode active material, acetylene black (1.5 parts by mass) as a conductive material, and PVdF (1 part by mass) as a binder was applied onto an aluminum foil (thickness: 12 μm) as a current collector to prepare a positive electrode. Table 1

[0042] As shown in Table 1, the single-unit capacity of the positive electrode of the example made of carbon particles and PTFE whose surfaces are at least partially coated with resin is larger than that of the positive electrode of the comparative example made of carbon particles and PTFE whose surfaces are not coated with resin. The above results suggest that coating the surface of carbon particles with a resin inhibits excessive formation of SEI on the surface of carbon particles, thereby contributing to an increase in the monomer capacity.

Claims

1. A method for manufacturing an electrode, the electrode being an electrode used in a battery containing an electrolyte, the manufacturing method comprising: A step of coating at least a portion of the surface of the carbon particles with a resin; A step of mixing carbon particles coated with a resin and polytetrafluoroethylene to obtain a mixture; as well as The step of fiberizing the polytetrafluoroethylene in the mixture.

2. The method for manufacturing an electrode according to claim 1, wherein: The coverage rate of the carbon particles by the resin is 3% or more.

3. An electrode used in a battery containing an electrolyte, It includes a current collector and an electrode layer, The electrode layer includes carbon particles and fibrous polytetrafluoroethylene, and at least a portion of the surface of the carbon particles is coated with a resin.

4. The electrode according to claim 3, wherein The coverage rate of the carbon particles by the resin is 3% or more. 5 . A battery comprising the electrode according to claim 3 or 4 and an electrolyte solution.

Citation Information

Patent Citations

  • Electrode film for energy storage device, electrode and energy storage device

    JP2022003694A